Understanding the nature of atmospheric acid processing of mineral dusts in supplying bioavailable phosphorus to the oceans - Stockdale, A; Krom, MD; Mortimer, RJG; Benning, LG; Carslaw, KS; Herbert, RJ; Shi, Z; Myriokefalitakis, S; Kanakidou, M; Nenes, A (National Academy of Sciences, 2016)
Acidification of airborne dust particles can dramatically increase the amount of bioavailable phosphorus (P) deposited on the surface ocean. Experiments were conducted to simulate atmospheric processes and determine the dissolution behavior of P compounds in dust and dust precursor soils. Acid dissolution occurs rapidly (seconds to minutes) and is controlled by the amount of H + ions present. For H + < 10 −4 mol/g of dust, 1–10% of the total P is dissolved, largely as a result of dissolution of surface-bound forms. At H + > 10 −4 mol/g of dust, the amount of P (and calcium) released has a direct proportionality to the amount of H + consumed until all inorganic P minerals are exhausted and the final pH remains acidic. Once dissolved, P will stay in solution due to slow precipitation kinetics. Dissolution of apatite-P (Ap-P), the major mineral phase in dust (79–96%), occurs whether calcium carbonate (calcite) is present or not, although the increase in dissolved P is greater if calcite is absent or if the particles are externally mixed. The system was modeled adequately as a simple mixture of Ap-P and calcite. P dissolves readily by acid processes in the atmosphere in contrast to iron, which dissolves more slowly and is subject to reprecipitation at cloud water pH. We show that acidification can increase bioavailable P deposition over large areas of the globe, and may explain much of the previously observed patterns of variability in leachable P in oceanic areas where primary productivity is limited by this nutrient (e.g., Mediterranean).